Theories of International Relations and the Explanation of Foreign Aid - PAUSELLI, Gino (Revista Iberoamericana de Estudios de Desarrollo)
50 years after the publication of the first and influential article in international relations (IR) analyzing foreign aid motivations, A theory of foreign aid, by Hans Morgenthau, IR scholarship has not yet accomplished a consistent theoretical body explaining international development cooperation. Most of the empirical studies on foreign aid have been contributions from other disciplines, especially economics. Research from the field of international relations has been mostly descriptive or poorly connected with IR paradigms.This article proposes to analyze motivations of foreign aid allocations decisions of donors. These motivations will be examined from the theoretical perspective of the international relations scholarship. In this way, it is sought to contribute, from the discipline of IR, to the explanation of the process in which developed countries make transfers of resources to developing countries.